The Contribution of Women in Improving Family Economic Resilience through the Banang Sahalai Knitting Community in Dadok Tunggul Hitam Village, Padang - Selvianti, Rivie; Montessori, Maria (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
This research is motivated by the fact that the economic contribution of women to their families is also very helpful for the economic resilience of the family itself. With the contribution of women to the family economy, it is also expected to have good participation in decision-making in the family. This study aims to analyze and identify: the contribution of women members of the banang sahalai knitting community in increasing family resilience in the economy, women's strategies in managing their involvement in the banang sahalai knitting community, and the impact of women's involvement in the banang sahalai knitting community on their participation in decision making in the family. To discuss this research problem, the theory of socialist feminism is used. The approach used is qualitative with descriptive type. Research informants were determined by the purposive sampling technique. Data was collected using observation, interviews, and document studies. Validity test using triangulation technique. Analysis of the data using the interactive analysis model of Miles and Huberman. The results show that in increasing economic resilience, women act as financial producers for the family and manage household income. The contribution of women in increasing the economic resilience of the family is inseparable thanks to the joining of women in a community, namely Banang Sahalai. So to manage their involvement in the banang sahalai knitting community, women have certain strategies. So that with the existence of women in the community and increasing the economic resilience of the family,